KARAKTERISASI MIKROKAPSUL ASAP CAIR TEMPURUNG KELAPA DENGAN PENYALUT DEKSTRIN SORGUM, JAGUNG DAN BEKATUL BERAS - , Tari Apriliani ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Redestilation of coconut shell liquid smoke used to preserve of natural food, but it can damage during storage and less practically in handling, application and distribution. Spray drying was a method to maintain its potency, improved handling, applications and distribution of liquid smoke redestilation encapsulation. Dextrin from sorghum, corn and rice bran were coating agent for redestilation of coconut shell liquid smoke encapsulation. Dextrin sorghum, corn and rice bran were expected to provide the properties and quality of coconut shell liquid smoke redestilation microcapsules. The objectives of this study were to investigate the properties and quality of liquid smoke redestilation microcapsule using dextrin from sorghum, corn, and rice bran as wall materials. Encapsulation of coconut shell liquid smoke redestilation was carried out using spray drying with inlet/outlet temperature of 130/65ÂºC, respectively, feed flow rate of 5 mL/minute with total soluble solid/TSS of sorghum, corn and rice bran dextrin are 20, 25 and 30% w/v. Evaluation parameters were phenolic staining, moisture content, yield, total phenolic compound, efficiency, morphology, particle size distribution and volatile profile identification. Data was taken triplicate for all parameters using completely randomized experiment design. The best result was obtained using TSS of dextrin from sorghum and corn 20% w/v as well as TSS of rice bran 30% w/v. Increasing of total soluble solid could decrease total phenolic, efficiency and yield of coconut shell liquid smoke microcapsule using sorghum and corn dextrin, excepted rice bran dextrin. Microcapsule morphology showed that particles less homogenity and agglomerated. The particle size of sorghum dextrin 20% w/v was small and retension of volatile compound was good.